THE FACTORS OF WRITING ACHIEVEMENT OF STUDENTS AT SMP WAHID HASYIM BASED ON THEIR LEARNING STYLES - Wa Rahayu (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: The purpose of this study is to find factors of writing achievement based on their learning styles. There are two problems to be solved: (1) What are the factors that cause students to have good writing achievement based on their learning styles (VAK) and (2) what are the factors cause students to have poor writing achievement based on their learning styles (VAK). The method in this study was qualitative study. The subjects of this study were twenty-five students in a second-grade language class at SMP Wahid Haysim. The researcher collected the data from the Perceptual Learning Style Preferences (PLSP) questionnaire from Reid (1984), the interview guide was conducted by using a semi-structural and the type of this interview was opened-ended. The data were analyzed by grouping the students based on their learning styles, explaining the data from the questionnaire and interview sheet, and drawing conclusions based on the research problems and results of the data analysis. The finding of this study shows that the auditory learning style becomes the most learning style preference by the students followed by visual and kinesthetic. Furthermore, the factors that cause students to have good writing achievements are: (1) students’ learning preferences, (2) students’ different learning styles, and (3) students’ internal, external, and Learning Approaches. The factors that cause students to have poor writing achievement are: (1) no skill in writing, uninterested, vocabulary mastery and no ability to write in English (2) Internal, External, and Learning Approaches. Keywords: factors of students' writing achievement, learning styles